ELDERLY PARENTS AND INTERNATIONAL MIGRATION OF SONS: E VIDENCE FROM PAKISTA N AND AZAD JAMMU & KASHMIR - Asia ASHFAQ (Journal of Identity and Migration Studies, 2016)
This paper aims to explore the relation between international migration of male children and the the parents left behind. The premise was to investigate how the international migration of male children affects the family and social life, financial security and health of the parents left behind. For this purpose, using qualitative research design In-Depth Interviews (IDI) were conducted with four parents selected purposively whose male children had migrated abroad. Moreover, interview guide was used as research instrument for collecting the data and narrative analysis has been done to make sense of the data. Two cities namely Gujrat (Pakistan) and Mirpur (Azad Jammu & Kashmir) were selected on the basis of existing higher trend of international migration in these regions. The findings reveal that the respondents’ children were living abroad for more than 15 years and their children were involved in skilled labour work. The parents reported to have feelings of sadness, isolation, depression and loneliness in the absence of their children. The findings also unleashed the coping strategies used by left behind parents for lessening their suffering.